The Effect of Mathematical Language On Learning Mathematics - Wahyuni, Priska; Pangestu, Saka Aji; Mursyida, Itsna Shalihatus Sabila; Pangestu, Aji (Proceeding International Conference on Science and Engineering, 2020)
Language as a communication tool has an important role in interaction between human beings. Language can be used by humans to convey ideas, ideas, desires, feelings and experiences to others. Especially in a learning activity where communication tools such as language must be clearly and easily understood. In learning mathematics, the language of mathematics is very important in helping the learning process. Because to understand mathematical concepts easily requires mathematical language skills. However, the situation on the ground shows that students' understanding of mathematical language is not optimal. This study aims to determine the effect of students' mathematical language on understanding material. So the results of this study can be used by teachers as a reference in teaching mathematics to students and teachers become more concerned with students' mathematical language abilities. The method used in this study is the study of literature, which examines relevant previous studies and concludes based on the results obtained. The results of this study are that if students have understood the language of mathematics well, students can receive and understand the material easily and can increase student interest in learning. So indirectly high mathematical language skills can improve students' mathematical ideas to be more structured and convincing. Moreover, on material related to many symbols such as algebra. In addition, students can receive and understand the material easily and student interest in learning will increase.